The short form 36 health status questionnaire: clues from the Oxford region's normative data about its usefulness in measuring health gain in population surveys. - Ziebland, S (1995)
OBJECTIVES: To determine the potential of the short form 36 health status questionnaire (SF-36) for indicating changes in the health status of a general population by examining the recently published normative data. DESIGN: The sensitivity of the SF-36 was tested through hypothesising two dramatic changes in health status whereby (i) the scores of people in social class V are improved to the level of social class I, and (ii) the scores of men and women aged 55 to 64 are altered to the level of current 45 to 54 year olds. The size of the effect measured by the SF-36 was considered. RESULTS: Small to moderate effects were evident when SF-36 mean scores for social class V were increased to the level of social class I, and primarily negligible effects were apparent on all domains but physical function for the postulated "10 years of age" improvement. CONCLUSION: The SF-36 may be a useful measure for detecting changes in health status in homogenous treatment groups, but the variation in responses in a general population make it an inadequate tool for assessing the diffuse impact of health interventions directed at the whole community.